2008
DOI: 10.1086/587743
|View full text |Cite
|
Sign up to set email alerts
|

A Long Look at the Be/X‐Ray Binaries of the Small Magellanic Cloud

Abstract: -We have monitored 41 Be/X-ray binary systems in the Small Magellanic Cloud over ∼ 9 years using PCA-RXTE data from a weekly survey program. The resulting light curves were analysed in search of orbital modulations with the result that 10 known orbital ephemerides were confirmed and refined, while 10 new ones where determined. A large number of X-ray orbital profiles are presented for the first time, showing similar characteristics over a wide range of orbital periods. Lastly, three pulsars: SXP46.4, SXP89.0 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
185
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(212 citation statements)
references
References 67 publications
27
185
0
Order By: Relevance
“…Rajoelimanana et al (2011b) analysed the OGLE III data, which revealed a significant peak at 171 ± 0.3 d in the power spectra, which is less than half the reported X-ray period. Galache et al (2008) already noted that the X-ray period is longer than would be expected given its spin period position in the Corbet diagram (Corbet 1984;Laycock et al 2005, see also Fig. 8, in which SXP82.4 is found as the right-most open red circle).…”
Section: Update On Individual Bexrb Pulsarsmentioning
confidence: 86%
See 2 more Smart Citations
“…Rajoelimanana et al (2011b) analysed the OGLE III data, which revealed a significant peak at 171 ± 0.3 d in the power spectra, which is less than half the reported X-ray period. Galache et al (2008) already noted that the X-ray period is longer than would be expected given its spin period position in the Corbet diagram (Corbet 1984;Laycock et al 2005, see also Fig. 8, in which SXP82.4 is found as the right-most open red circle).…”
Section: Update On Individual Bexrb Pulsarsmentioning
confidence: 86%
“…Description Liu et al (2005) HMXB catalogue of the Magellanic Clouds Coe et al (2005) Optical properties of HMXBs in the SMC Shtykovskiy & Gilfanov (2005) HMXBs in archival XMM-Newton data McGowan et al (2008b) Chandra SMC Wing survey Galache et al (2008) RXTE observations of SMC pulsars McBride et al (2008) Optical spectroscopy of BeXRB pulsars in the SMC New BeXRBs from XMM-Newton observations in Antoniou et al (2009b Optical identification of Chandra sources Antoniou et al (2009a) Optical spectroscopy of BeXRBs in the SMC Laycock et al (2010) Catalogue of SMC sources from deep Chandra observations a Rajoelimanana et al (2011b) Long-term optical variability of HMXB pulsars in the SMC Sturm et al (2013c) XMM-Newton survey of the SMC Coe & Kirk (2015) BeXRB pulsars in the SMC Notes. (a) Includes detections down to two net counts.…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…(SMC) was monitored with RXTE for about 14 years (Galache et al 2008). Therefore, only nine HMXB X-ray pulsars are known to date in the LMC, which inhibits a statistical comparison of this sample with those of the Galaxy and the SMC.…”
Section: Introductionmentioning
confidence: 99%
“…Corcoran 2005) or enhanced accretion rates in X-ray binaries (e.g. Galache et al 2008). Such repetitive, periodic flaring is not immediately apparent in the lightcurve of VFTS 399, although this does not preclude its future occurrence since, in the case of X-ray binaries, such behaviour is observed to be transient.…”
Section: Lombmentioning
confidence: 99%